Implementasi Full Day School pada Madrasah Tsanawiyah Negeri 3 Aceh Barat - Hasnadi Hasnadi; Irya Zalina (Universitas Indraprasta PGRI Jakarta, 2022)
Full day school is the implementation of 8 hours teaching and learning process in the schools per day from Monday to Friday. It aims at developing students’ full potential, strengthening character building, improving the quality of education. However, the goal of implementing full day school will not be achieved optimally if it is not managed properly. The purpose of this study was to describe and analyze the implementation of full day school. it was performed as a case study under a qualitative research approach. The research subjects were the head and deputy madrasah, teachers and students. Data was collected by interviews, observation and documentation. Data analysis was carried out through the stages of data reduction, data display, verification and conclusion. The results of the study concluded that the preparation carried out by madrasahs in the implementation of full day school is holding regular and scheduled meetings involving all school personnel, parents/guardians of students and madrasah committees. Through meeting activities, programs and schedules for implementing activities will be determined as well as preparing supporting facilities taking into account the available funds. The activity programs carried out are based on the implementation of character values and the development of the potential possessed by students. The Covid-19 pandemic has an impact on the implementation of full day school so that programs are not carried out according to plan.